Studi Eksperimental Pengaruh Konfigurasi Rangkaian terhadap Daya Listrik Paving Blok Piezoelektrik (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The increasing demand for electrical energy each year and the high dependence on fossil energy, which has negative environmental impacts, necessitate the development of alternative renewable energy sources. One potential source that can be utilized is mechanical energy from human activities through the application of piezoelectric technology in paving blocks. In addition, studies on the effect of piezoelectric circuit configurations, particularly comparisons between series and parallel circuits in generating electrical power, are still limited. This study employed an experimental method using a piezoelectric paving block prototype, with testing conducted under a static load of 60 kg. The measured parameters included output voltage and current, which were then used to calculate the generated power. The experimental results show that the parallel circuit configuration produced a higher average electrical power of 1.51 mW compared to the series circuit, which generated an average power of 1.37 mW. The increase in power in the parallel configuration was mainly influenced by the higher output current, while the difference in voltage was relatively insignificant. These findings contribute to determining a more optimal circuit configuration for the development of piezoelectric paving blocks as a renewable energy harvesting system based on mechanical pressure.